Long‐Term Follow‐up of Small Pulmonary Ground‐Glass Nodules Stable for 3 Years: Implications of the Proper Follow‐up Period and Risk Factors for Subsequent Growth. Issue 9 (September 2016) - Cho, Jaeyoung; Kim, Eun Sun; Kim, Se Joong; Lee, Yeon Joo; Park, Jong Sun; Cho, Young‐Jae; Yoon, Ho Il; Lee, Jae Ho; Lee, Choon‐Taek
ABSTRACT : Introduction: : How long persistent and stable ground‐glass nodules (GGNs) should be followed is uncertain, although a minimum of 3 years is suggested. Here, we evaluated a group of GGNs that had remained stable for an initial period of 3 years with the aim of determining the proportion of GGNs showing subsequent growth after the initial 3 years and identifying the clinical and radiologic factors associated with subsequent growth. Methods: : We retrospectively analyzed patients who underwent further computed tomography (CT) after the initial 3‐year follow‐up period showing a persistent and stable GGN (at least 5 years of follow‐up from the initial CT). Results: : Between May 2003 and June 2015, 453 GGNs (438 pure GGNs and 15 part‐solid GGNs) were found in 218 patients. Of the 218 patients, 14 had 15 GGNs showing subsequent growth after the initial 3 years during the median follow‐up period of 6.4 years. For the person‐based analysis, the frequency of subsequent growth of GGNs that had been stable during the initial 3 years was 6.7% (14 of 218). For the nodule‐based analysis, the frequency was 3.3% (15 of 453). In a multivariate analysis, age 65 years or older (OR = 5.51, p = 0.012), history of lung cancer (OR = 6.44, p = 0.006), initial size 8 mm or larger (OR = 5.74, p = 0.008), presence of a solid component (OR = 16.58, p = 0.009), and air bronchogram (OR = 5.83, p = 0.015) were independent risk factors for subsequent GGN growth. Conclusions: : For the individuals with GGNs having the aforementioned risk factors, the longer follow‐up period is required to confirm subsequent GGN growth.